Chemistry solution study of gaharu water-mixture - Nurul Salwa Azliyana, Hamzah (2013)
This research is about chemistry solution study of Gaharu-water mixture. The fundamental of chemistry properties of Gaharu-water mixture will be investigated by using Preparative High Performance Liquid Chromatography (PREP-HPLC) and Fourier Transform Infrared Spectroscopy (FTIR). This will give benefits for the development of economics and help the engineers provide the accurate properties of Gaharu compound solubility in water. Then, the gaharu marker compound characterized from gaharu water mixture may provide the useful information to engineers and scientists to give an insight to control the gaharu extraction process in a better way. The first objective of the study is to develop the method (protocol) in identify and recognize the Gaharu marker compound in water mixture. The second objective if this research is to identify the compound and molecular chemistry of Gaharu oil via Fourier Transform Infrared Spectroscopy (FTIR) and Preparative High Performance Liquid Chromatography (PREP-HPLC). As the conclusion, Gaharu marker compound that dissolve in the water mixture can be successfully identified by using FTIR and PREP-HPLC. Main marker compound dissolved in water are agarospirol, jinkohol-eremol, jinkohol and kusenol.